Peran Pendidikan Kewarganegaraan dalam Menguatkan Etika Digital dan Kesadaran Sosial Mahasiswa di Era Media Sosial - Dahniar Dahniar; Syamzaimar Syamzaimar (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2026)
This study aims to analyze the role of civic education in strengthening digital ethics and enhancing students’ social awareness in the era of social media. The rapid development of information technology has created both opportunities and challenges, particularly for students as active social media users. Using a qualitative approach, this research employed in-depth interviews, focus group discussions, and participatory observations involving students who had completed civic education courses. Thematic analysis was applied to identify behavioral patterns, which were then categorized based on their relevance to digital ethics and social awareness.The findings reveal that civic education plays a significant role in shaping students’ digital behavior to be more ethical, critical, and responsible. Students with strong civic knowledge tend to be more cautious in sharing information, respect privacy, and engage actively in constructive discussions. Moreover, social media serves as an effective platform for fostering solidarity and social concern, although challenges such as misinformation and hate speech remain prevalent. This study highlights the urgent need to integrate civic education with digital literacy, enabling students to navigate the complexities of the digital world wisely.